Entwicklungspläne in der Gambia - Manshard, Walther (ERDKUNDE, 1955)
This article describes recent development plans in the Gambia, the smallest of the four British West African colonies. Various projects e.g. the Gambia Poultry Scheme, the Rice Scheme and a fisheries project are discussed. Experience in the Gambia has helped to convince even the most optimistic of colonial planners that development on the cheap and on the quick is impossible in Africa. These post-war failures have given rise to a more sober attitude: pilot and research schemes (soil, land-use, agriculture, etc.) are now being undertaken. The past has proved that the question is not whether a small colony like the Gambia can afford such preliminary investigations, but whether it can afford not to have them. In spite of all these, which include the recent introduction of ilmenite mining, the Gambia still has to rely mainly on its ground nut production. In this connection, the interesting contribution of the strange farmer is underlined.